Endogenous Long Pentraxin 3 Exerts a Protective Role in a Murine Model of Pulmonary Fibrosis - Maccarinelli, Federica; Bugatti, Mattia; Churruca Schuind, Ander; Ganzerla, Sara; Vermi, William; Presta, Marco; Ronca, Roberto (Frontiers in Immunology, 2021)
Pulmonary fibrosis is a progressive scarring disease of the lungs, characterized by inflammation, fibroblast activation and deposition of extracellular matrix. The long pentraxin 3 (PTX3) is a member of the pentraxin family with non-redundant functions in innate immune responses, tissue repair, and haemostasis. The role played in the lungs by PTX3 during the fibrotic process has not been elucidated. In this study, the impact of PTX3 expression on lung fibrosis was assessed in an intratracheal bleomycin (BLM)-induced murine model of the disease applied to wild type animals, transgenic mice characterized by endothelial overexpression and stromal accumulation of PTX3 (Tie2-PTX3 mice), and genetically deficient Ptx3-/- animals. Our data demonstrate that PTX3 is produced during BLM-induced fibrosis in wild type mice, and that PTX3 accumulation in the stroma compartment of Tie2-PTX3 mice limits the formation of fibrotic tissue in the lungs, with reduced fibroblast activation and collagen deposition, and a decrease in the recruitment of the immune infiltrate. Conversely, Ptx3-null mice showed an exacerbated fibrotic response and decreased survival in response to BLM treatment. These results underline the protective role of endogenous PTX3 during lung fibrosis and pave the way for the study of novel PTX3-derived therapeutic approaches to the disease.